Economic costs of ocean acidification: A look into the impacts on shellfish production - Daiju Narita; Katrin Rehdanz; Richard S. J. Tol (Kiel Institute for the World Economy (IfW), 2011)
Ocean acidification is increasingly recognized as a major global problem. Yet economic assessments of its effects are currently almost absent. Unlike most other marine organisms, mollusks, which have significant commercial value worldwide, have relatively solid scientific evidence of biological impact of acidification and allow us to make such an economic evaluation. By performing a partial-equilibrium analysis, we estimate global and regional economic costs of production loss of mollusks due to ocean acidification. Our results show that the costs for the world as a whole could be over 100 billion USD with an assumption of increasing demand of mollusks with expected income growths. The major determinants of cost levels are the impacts on the Chinese production, which is dominant in the world, and the expected demand increase of mollusks in today's low-income countries, which include China, in accordance with their future income rise.
Keywords: Q51; Q54; Q57; 330; Climate Change; Economic Impact; Mollusks; Ocean Acidification; Meeresverschmutzung; Klimaveränderung; Meerestier; Soziale Kosten; Welt; China